2019
DOI: 10.1038/s41598-019-53268-1
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Zn and its Binding Protein Zinc-α2-Glycoprotein are Elevated in HPV-Positive Oropharyngeal Squamous Cell Carcinoma

Abstract: Human papillomavirus (HPV)-positive head and neck squamous cell carcinoma (HNSCC) is biologically distinct from HPV-negative HNSCC. Outside of HPV-status, few tumor-intrinsic variables have been identified that correlate to improved survival. As part of exploratory analysis into the trace elemental composition of oropharyngeal squamous cell carcinoma (OPSCC), we performed elemental quanitification by X-ray fluorescence microscopy (XFM) on a small cohort (n = 32) of patients with HPV-positive and -negative OPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…In this study, the oral squamous cell carcinoma samples that showed positive staining for Zinc Alpha-2 Glycoprotein (ZAG) belonged to the early stages (I and II) and of a moderately differentiated variant. This is in accordance with Poropatich et al study; they have also found high expression of ZAG in the early stages and moderately differentiated oropharyngeal squamous cell carcinoma 17 . Similarly, other studies have also reported higher expression of ZAG in well-differentiated oral squamous cell carcinoma and reduced in poorly differentiated tumors [18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the oral squamous cell carcinoma samples that showed positive staining for Zinc Alpha-2 Glycoprotein (ZAG) belonged to the early stages (I and II) and of a moderately differentiated variant. This is in accordance with Poropatich et al study; they have also found high expression of ZAG in the early stages and moderately differentiated oropharyngeal squamous cell carcinoma 17 . Similarly, other studies have also reported higher expression of ZAG in well-differentiated oral squamous cell carcinoma and reduced in poorly differentiated tumors [18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
“…Irradiated tissues showed decreased concentrations of S, K, Ca, Fe, and Zn regardless of the dose used. Considering that elemental concentration perturbations correlate with differences in radiation sensitivity, this study may be opening a new area of investigation for radiation studies (Poropatich et al 2019).…”
Section: Elementalomicsmentioning
confidence: 97%
“…Silicon drift energy dispersive detector positioned was used to collect the fluorescence signal from samples, at 90 • to the incident beam. Per pixel elemental concentration was obtained by comparison with the thin-film standards NBS-1832 and NBS-1833 from the National Bureau of Standards (Gaithersburg, MD), and the analysis was done using MAPS software (38) as detailed in other studies (20,(34)(35)(36).…”
Section: X-ray Fluorescence Microscopymentioning
confidence: 99%
“…We have used this animal model for different types of studies for more than 15 years (14,20,23,(26)(27)(28)(29)(30)(31). Over the same period, we have also worked on introducing a unique imaging technique, x-ray fluorescence microscopy (XFM), into pathology (20,(32)(33)(34)(35)(36). Although we have previously used XFM to image liver VX2 samples (20), this is the very first study where we have developed and implemented necessary sample preparation techniques to process radioactive tissue samples and make them suitable for XFM imaging.…”
Section: Introductionmentioning
confidence: 99%